Selective Hydrogenation of Furfural in a Proton Exchange Membrane Reactor Using Hybrid Pd/Pd Black on Alumina. Issue 22 (25th October 2019) - Carl, Sarah; Waldrop, Krysta; Pintauro, Peter; Thompson, Levi T.; Tarpeh, William A.
Abstract: Invited for this month's cover picture are the groups of Dr. Peter Pintauro (Vanderbilt University, Tennessee, USA), Dr. Levi Thompson (University of Delaware, Delaware, USA), and Dr. William Tarpeh (Stanford University, California, USA). The cover picture shows the controlled variation of furfural hydrogenation product speciation based on varying cathode formulations of hybrid Pd black and Pd on alumina support. Read the full text of the article at 10.1002/celc.201901314 . Abstract : "The performance of different cathode compositions is evaluated at different current densities (which varies with hydrogen production) in terms of production rate, faradaic efficiency, and selectivity. To isolate the influences of the electrocatalyst in the hybrid catalyst, the performance of electrocatalyst Pd black is evaluated separately. These four variations of the hybrid cathode are investigated to test the hypothesis that the addition of the metal loaded on metal oxide to the electrocatalyst enhances the production rate for hydrogenated products compared to electrodes with only an electrocatalyst…" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Article at 10.1002/celc.201901314 .